A hiatus in the rivalry between Pierre Marie and Jules Dejerine: a collaborative study on sensory disorders by Andre Pierre Marie and Gustave Roussy - Carlos Henrique Ferreira Camargo; Emanuel Cassou; Francisco Manoel Branco Germiniani; Hélio Afonso Ghizoni Teive (Arquivos de Neuro-Psiquiatria)
Personal and professional rivalries involving prominent neurologists mark the history of nineteenth-century French neurology. One of the great examples is the feud between Pierre Marie and Jules Dejerine. The dispute between the two, nevertheless, did not prevent Pierre Marie's son, André Marie, and Gustave Roussy – one of Dejerine's favorite pupils, from collaborating on significant research that led to the doctoral dissertation by Andre Marie regarding sensory disturbances associated with painful hemiagnosia found in thalamic lesions.